La sección de creación en la revista interface: Veinte años de experimentación - de Castro, Eliane Dias; de Almeida, Eduardo Augusto Alves; Asanuma, Gisele Dozono; Silva, Juliana Araújo [UNESP]; Buelau, Renata Monteiro; Quarentei, Mariangela Scaglione; Teixeira, Ricardo Rodrigues; Lima, Elizabeth Maria Freire Araújo (FapUNIFESP (SciELO), 2017)
To celebrate the 20th anniversary of the journal Interface, members of the team responsible for the Creation section immersed themselves in a range of materials that have been published in the section since the journal’s very first issue. The result is an assortment of images, words and reflections that gives an insight as to the multiplicity of voices that tell this story. They represent attempts to think about the Creation section both nowadays and in the past, along with possible pathways for its on-going - and essential - reinvention.
A seção de criação na revista interface: Vinte anos de experimentação
The section on creation at the journal interface: Twenty years of experimentation
Keywords: Creation; Health research; Interdisciplinarity; Languages; Publishing group